"Part of My Daily Life": The Importance of Public Libraries as Physical Spaces. Issue 2 (4th March 2023) - Hider, Philip; Garner, Jane; Wakeling, Simon; Jamali, Hamid R.
ABSTRACT: The COVID-19 pandemic provided a unique opportunity to gauge how much, and why, people value visiting public libraries by asking them about the impact of the library closures. A questionnaire survey was administered to users of four library networks in New South Wales, Australia. About 19% of 1, 295 respondents missed their library "a great deal, " another 28% "quite a lot." Most commonly respondents missed browsing the shelves, taking children for visits, studying, reading, and socializing there. They also missed the quiet, relaxing, and friendly environment, and the resources provided. For many, the closures impacted their lives in a critical way.